Plant Products as Inhibitors of Coronavirus 3CL Protease - Mandal, Anirban; Jha, Ajeet Kumar; Hazra, Banasri (Frontiers in Pharmacology, 2021)
Background: The ongoing COVID-19 pandemic has created an alarming situation due to extensive loss of human lives and economy, posing enormous threat to global health security. Till date, no antiviral drug or vaccine against SARS-CoV-2 has reached the market, although a number of clinical trials are under way. The viral 3-chymotrypsin-like cysteine protease (3CLpro), playing pivotal roles in coronavirus replication and polyprotein processing, is essential for its life cycle. In fact, 3CLpro is already a proven drug discovery target for SARS- and MERS-CoVs. This underlines the importance of 3CL protease in the design of potent drugs against COVID-19. Methods: We have collected one hundred twenty-seven relevant literatures to prepare the review article. PubMed, Google Scholar and other scientific search engines were used to collect the literature based on keywords, like “SARS-CoVs-3CL protease,” “medicinal plant and anti-SARS-CoVs-3CL protease” published during 2003–2020. However, earlier publications related to this topic are also cited for necessary illustration and discussion. Repetitive articles and non-English studies were excluded. Results: From the literature search, we have enlisted medicinal plants reported to inhibit coronavirus 3CL protease. Some of the plants like Isatis tinctoria L. (syn. Isatis indigotica Fort.), Torreya nucifera (L.) Siebold and Zucc., Psoralea corylifolia L., and Rheum palmatum L. have exhibited strong anti-3CLpro activity. We have also discussed about the phytochemicals with encouraging antiviral activity, such as, bavachinin, psoralidin, betulinic acid, curcumin and hinokinin, isolated from traditional medicinal plants. Conclusion: Currently, searching for a plant-derived novel drug with better therapeutic index is highly desirable due to lack of specific treatment for SARS-CoV-2. It is expected that in-depth evaluation of medicinally important plants would reveal new molecules with significant potential to inhibit coronavirus 3CL protease for development into approved antiviral drug against COVID-19 in future.